Analysis Of Marketing Content Strategies On Instagram Lucky Fit Club Kediri In Increasing Brand Awareness - Maharani, Elok Cahya; Sardanto, Rino (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : To analyze how content published on the platform can increase brand awareness among the audience and to determine the effectiveness of various types of content used such as images, videos and stories in attracting attention and building relationships with followers. As well as maintaining increased insight into Instagram features such as number of viewers, likes, shares Design/Methode/Approach : Uses a descriptive qualitative approach to analyze the content marketing strategy implemented by Lucky Fit Club on Instagram in an effort to increase brand awareness. This method was chosen because of its ability to provide deep insight into the audience's experiences and perceptions of the content presented. Data was collected through in-depth interviews with Instagram account managers, observing the type and frequency of content, and analyzing interactions on the platform. The research results show that a content strategy that includes careful planning, the use of attractive visuals, and consistency in posting frequency has proven to be effective in increasing brand awareness, as measured by increasing the number of followers and interactions. These findings provide recommendations for Lucky Fit Club to continue exploring new types of content and conducting regular analysis of content performance. This research is expected to contribute to the development of marketing strategies in the fitness and health industry [1]. Research Finding : In this research, I found that the content marketing strategy implemented by Lucky Fit Club Kediri on Instagram significantly increased brand awareness and audience engagement. With a structured approach, including clear goal setting, precise audience mapping, and relevant content creation, Lucky Fit Club managed to attract attention and build a strong community around their brand [2]. Theoretical contribution/Originality : This research provides an important theoretical contribution by adding insight into the application of content marketing strategies on social media, especially in the context of the fitness industry in Indonesia. The novelty of this research lies in its specific focus on the use of Instagram as a marketing tool, which is still rarely discussed in the existing literature. Thus, this research enriches the understanding of the dynamics of digital marketing in the fitness sector. Practitionel/Policy implication : The practical implications of this research show that fitness industry players and other businesses can utilize Instagram as an effective platform for increasing brand awareness and audience engagement. I recommend that businesses adopt a structured approach to designing and managing content, and undertake ongoing content evaluation and development to maintain relevance in a competitive marketplace [3]. Research limitation : Limitations of this study include limited audience coverage and short study time, which may affect the generalizability of the findings. In addition, this research does not consider external factors that can influence the effectiveness of content marketing strategies. For further research, I plan to expand the audience reach and observe the long-term impact of the strategies implemented, as well as explore the comparison between various social media platforms in a marketing context.